Clinical parameters predictive of outcomes in sorafenib‐treated patients with advanced hepatocellular carcinoma. (21st April 2013) - Cho, Ju‐Yeon; Paik, Yong‐Han; Lim, Ho Yeong; Kim, Young Gon; Lim, Hyo Keun; Min, Yang Won; Gwak, Geum‐Youn; Choi, Moon Seok; Lee, Joon Hyeok; Koh, Kwang Cheol; Paik, Seung Woon; Yoo, Byung Chul
Abstract Background Sorafenib is an orally active multikinase inhibitor approved for the treatment of advanced hepatocellular carcinoma (HCC). However, clinical parameters that may predict the treatment outcomes in sorafenib‐treated advanced HCC patients remains unknown. Methods A total of 99 advanced (BCLC C) HCC patients treated with sorafenib as an initial treatment modality from January 2007 to December 2011 were retrospectively reviewed. Overall survival was the primary endpoint for the analysis. Various clinical parameters including tumour stage and adverse effects to sorafenib were analysed. Univariate and multivariate analysis were carried out to identify clinical parameters predictive of the effect of sorafenib. Results There were 86 males and 13 females included in this study, with a median age of 53 years. The median overall survival was 91 days. Sixty‐nine patients had Child‐Pugh class A cirrhosis and 30 patients had Child‐Pugh class B cirrhosis. Hepatitis B virus was the predominant cause of HCC (75.8%). Noted adverse effects were hand‐foot syndrome, diarrhoea, fatigue, abdominal pain, nausea and stomatitis. The presence of hand‐foot syndrome and diarrhoea and the absence of portal vein thrombosis and lymph node metastasis predicted a better overall survival in the multivariate analysis. Excluding the absence of lymph node metastasis, the same parameters were associated with a longer radiological time to progression. Conclusion Advanced HCC patients treated with sorafenib who experienced hand‐foot syndrome and diarrhoea showed better overall survival than patients without these side effects. These side effects may be used as clinical parameters predictive of sorafenib response in patients with HCC.